2015
DOI: 10.1186/s40064-015-0970-2
|View full text |Cite
|
Sign up to set email alerts
|

Immune cells subpopulations in cerebrospinal fluid and peripheral blood of patients with Aneurysmal Subarachnoid Hemorrhage

Abstract: BackgroundThere is growing evidence supporting the role of inflammation in aneurysmal subarachnoid hemorrhage (aSAH) pathophysiology and it is of great interest to elucidate which immune mechanisms are involved.Methods12 aSAH patients and 28 healthy controls were enrolled prospectively. We assessed leukocytes subpopulations and their activation status by flow cytometry in cerebrospinal fluid (CSF) and peripheral blood (PB) of SAH patients at the same time and in PB of controls.ResultsMonocytes and neutrophils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 73 publications
3
41
0
Order By: Relevance
“…42,43 Human studies have similarly shown increases in monocyte-associated genes after aneurysm rupture, 44 elevations in monocyte chemoattractant protein 1 in serum 45 and CSF 46 after SAH, and increase in activated monocytes identified by CSF and peripheral blood flow cytometry. 7 We further found that in those SAH patients with high sST2, there . Patients with aneurysmal rupture appear to have an increase in cells expressing transmembrane ST2 (tmST2) as well as the monocyte marker CD14, with subpopulations of CD16 and CD56 positive cells.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…42,43 Human studies have similarly shown increases in monocyte-associated genes after aneurysm rupture, 44 elevations in monocyte chemoattractant protein 1 in serum 45 and CSF 46 after SAH, and increase in activated monocytes identified by CSF and peripheral blood flow cytometry. 7 We further found that in those SAH patients with high sST2, there . Patients with aneurysmal rupture appear to have an increase in cells expressing transmembrane ST2 (tmST2) as well as the monocyte marker CD14, with subpopulations of CD16 and CD56 positive cells.…”
Section: Discussionmentioning
confidence: 58%
“…[37][38][39][40][41] Consistent with this, we found that aneurysm rupture and high levels of sST2 after rupture were associated with shifts in immune cell populations. 7 We further found that in those SAH patients with high sST2, there versus high sST2 at the early time point (defined as below or above the median value of 75ng/ml, n = 3 in each group). 42,43 Human studies have similarly shown increases in monocyte-associated genes after aneurysm rupture, 44 elevations in monocyte chemoattractant protein 1 in serum 45 and CSF 46 after SAH, and increase in activated monocytes identified by CSF and peripheral blood flow cytometry.…”
Section: Discussionmentioning
confidence: 63%
“…Recent evidence implicates neuroinflammation as a key mediator of injury expansion and behavioral deficits [ 3 , 4 ]. Peripheral immune cells are both recruited and activated in damaged tissue [ 5 ]. These cells can enter the brain parenchyma and release inflammatory cytokines [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only one preclinical study has shown neuroprotective effects of statins via upregulation of regulatory T lymphocytes in rodent SAH models (Ayer et al, 2013). Furthermore, only two clinical studies have shown proliferation of CD4+ and CD8+ T cells in CSF and peripheral blood of SAH patients (Mathiesen, Andersson, Loftenius, & Holst, 1993;Moraes et al, 2015). Due to the paucity of research, the clinical implications of the adaptive immune system in SAH remain unexplored.…”
Section: Adap Tive Immune Re S P On S E S To Sahmentioning
confidence: 99%